Designing a nurse-led assessment and care planning intervention to support frail older people in primary care: An e-Delphi study - Lyndon, H.; Latour, Jos; Marsden, J.; Kent, B. (WILEY, 2022)
Aim: To identify and establish expert consensus on important and feasible components of a nurse-led, comprehensive geriatric assessment (CGA)-based intervention for community-dwelling older people who live with frailty. Design: A three-round modified e-Delphi survey. Methods: An expert panel of 33 UK specialist older people's, primary and community care nurses participated in the three-round e-Delphi survey over a 12-month period in 2017–2018. Data from round 1 were analysed using content analysis. Descriptive statistics were used in the subsequent two rounds to demonstrate convergence of panel opinion and consensus. Results: In round 1, experts proposed 30 CGA components that were combined with six additional components from a literature review and clustered into six domains. In round 2, components were rated for importance and feasibility. Rating scores for importance were high across all domains, with lower scores for feasibility. Round 3 revealed that 36 components achieved consensus on importance and 11 out of 36 components reached consensus on feasibility. Conclusion: Based on expert panel opinion, the content of a nurse-led CGA-based intervention was established, with the aim of future feasibility testing in a randomized controlled trial. Impact: This study provides feasible components of a CGA-based intervention that can be implemented in clinical practice by nurses in partnership with older people who live with frailty. Following further testing and evaluation, the components have the potential to improve clinical outcomes, maximize independence and improve the quality of life for community-dwelling frail older people.